Carotid Artery Stenosis in Syncope and in Carotid Sinus Syndrome: A Few Concepts for the General Practitioner to Know - El-Alali, Emran; Abu-Halimah, Shadi; Maali, Laith; Alali, Yaman (Cardiology and Cardiovascular Medicine, 2021)
Background: In clinical practice, some investigations can have low diagnostic yield or little impact on treatment. Objectives: This article reviews the impact of asymptomatic carotid artery stenosis on management of syncope, and the role of carotid Doppler ultrasound in carotid sinus syndrome and in syncope. Unclear concepts in syncope workup and management are identified. Methods: We conducted a clinical survey of 206 internal medicine providers, to explore how many would consider unilateral carotid revascularization to treat isolated syncope, and how many would consider carotid ultrasound in evaluating carotid sinus syndrome. We searched the literature to identify cases in which carotid revascularization improved syncope, and whether or not carotid ultrasound was used to evaluate carotid sinus syndrome. Literature was reviewed for carotid ultrasound use in syncope. Results: 34% of medical providers surveyed considered carotid endarterectomy for isolated syncope treatment for unilateral high-grade carotid stenosis and 45% of surveyed providers considered carotid ultrasound in evaluating carotid sinus syndrome. The literature revealed older studies of syncope resolution following carotid endarterectomy in patients with specific characteristics; their detailed features are identified here, and revealed that evaluation of carotid sinus syndrome did not require carotid ultrasound. Conclusions: Carotid revascularization is not recommended for unilateral asymptomatic carotid artery stenosis to treat isolated syncope, and carotid ultrasound is not needed in the evaluation of carotid sinus syndrome and rates of neurological complications following carotid sinus massage were low.